The interplay and efficacy of the self-regulation and soft law mechanisms against the unfair competition in the International Trade Law - Ruiz Martín, Anna María (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
This paper analyses the efficacy and interplay of the different mechanisms of the Self-Regulation (Soft Law) in the International Trade Law to fight against the unfair commercial practices or unfair competition. These mechanisms, as it well known, are considered as quite controversial, taking into account their non-binding legal nature. It will be emphasized, despite the above mentioned, that these mechanisms actually, have a strong relationship with certain mechanisms of hard law set out in the International Trade Law which recognize the protection, up to a certain degree, against the unfair competition in the globalized market such as the Article 10 bis PC included in the TRIPS and some provisions of the GATT. Hence, it will be analysed the infraction of soft law rules against unfair competition, namely of the Social Corporate Responsibility and Compliance as a potential act of unfair competition such as a non-contractual obligation. In doing so, it could be reinforces these mechanisms with a more binding nature before the Courts, namely in international litigation against unfair competition.
Keywords: unfair competition; unfair commercial practices (B2B-B2C) self-regulation; compliance; Corporate Social Responsibility (CSR); international market; soft law; hard law; WTO; Article 10 bis PC; GATT; TRIPs; Codes of conduct